Pseudocalanus (Copepoda: Calanoida) of the North Atlantic Ocean : species composition, environmental preferences and phylogeography. - Aarbakke, O.N.S. (Ph.D. Thesis, University of Tromsø - The Arctic University of Norway (UIT), Tromsø, Norway, 2013)
The seven species of the genus Pseudocalanus (Copepoda: Calanoida) are difficult to identify because of very small interspecific, and comparatively large intraspecific, divergence of morphologic and morphometric traits. Thus, despite the fact that Pseudocalanus spp. are among the most abundant metazoans in the world, our knowledge of them at the species level is limited. The main objective of this thesis was to lay the groundwork for future studies of Pseudocalanus spp. in the Northeast Atlantic Ocean and Euro-Arctic by determining which species are present. Through a combined DNA barcoding and traditional identification approach, this work reveals the presence of at least four species of Pseudocalanus, one of which was previously not believed to occur in the East Atlantic Ocean. Furthermore, the thesis reveals differences in environmental preferences and distributions of Pseudocalanus elongatus, P. minutus, P. moultoni and P. acuspes in the Northeast Atlantic Ocean and Euro-Arctic, and discusses implications of these differences in relation to rising sea temperatures. Finally, this work examines the phylogeography and demographic history of Pseudocalanus minutus, P. moultoni, P. elongatus, P. acuspes and P. newmani in the North Atlantic Ocean and based on these results suggests an evolutionary hypothesis for the divergence of Pseudocalanus spp. into one oceanic and one coastal clade.